2014
DOI: 10.1590/s0102-67202014000400011
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and mortality of pancreatic tumors undergoing surgical treatment

Abstract: BackgroundPancreatic cancer has a high mortality rate due to late diagnosis and aggressive behavior. The prognosis is poor, with 5-year survival occurring in less than 5% of cases.AimTo analyze demographic characteristics, comorbidities, type of procedure and early postoperative complications of patients with pancreatic cancer submitted to surgical treatment.MethodsCross-sectional study with analysis of 28 medical records of patients with malignant tumors of the pancreas in a 62 month. Data collection was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 24 publications
0
18
0
3
Order By: Relevance
“…to pancreatic cancer in men, with 156,000 deaths in women. In developed countries, mortality rates are 7-9/100,000 in men and 4,5-6/100,000 in women (2,13) . The results presented herein showed that Brazilian mortality rates follow the behavior observed in developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…to pancreatic cancer in men, with 156,000 deaths in women. In developed countries, mortality rates are 7-9/100,000 in men and 4,5-6/100,000 in women (2,13) . The results presented herein showed that Brazilian mortality rates follow the behavior observed in developed countries.…”
Section: Resultsmentioning
confidence: 99%
“…This is because many patients do not experience symptoms until the disease is in an advanced stage, leading to delay in initiation of treatment 8 . Late presentation, tumor aggressiveness, difficult surgical resection, and availability of few effective systemic therapies contribute to the poor clinical outcome of pancreatic adenocarcinoma 9 . Egypt, as in many other developing countries, has little countrywide descriptive epidemiology about cancer including exocrine pancreatic adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic cancer is the twelfth most common type of cancer (2% of the total cases) and the seventh cause of cancer deaths worldwide [ 94 , 95 ]. Pancreatic cancer is not nearly as prevalent as lung or prostate cancers; however, pancreatic tumors are extremely aggressive, leading to the worst prognosis for any kind of cancer, with a five-year survival rate of ~5% [ 96 , 97 ]. Both exocrine and endocrine cells of the pancreas can form cancers, but those formed by exocrine cells are described to be much more common and aggressive [ 98 , 99 ].…”
Section: Microbiome and Pancreatic Cancermentioning
confidence: 99%